The development and evaluation of a web-based well-being intervention, for inclusion within an existing health promotion programme, to support and encourage health related lifestyle behaviour change - MENNA BROWN (2021)
Unhealthy lifestyle behaviours constitute a significant burden of disease, globally. Web-based interventions offer a means to support individuals in adopting and maintaining positive healthy lifestyle behaviours to address and reduce this issue. The health behaviour change literature offers several useful theoretical models which aim to explain or predict the likelihood of successful, individual level, lifestyle behaviour change. Indeed, research findings have shown that digital health interventions informed by these models are more likely to be effective. However, in practice adherence and engagement to web-delivered interventions is often critically low and is associated with reduced effectiveness and cost effectiveness. This thesis developed an emotional well-being intervention (ACTivate your Well-being), for inclusion within an existing lifestyle behaviour change programme ‘Champions for Health’. Thirty-eight anticipated end-users and six stakeholders contributed to a three-staged Participatory Design project which led to the development of a twelve-week intervention, based on Acceptance and Commitment Therapy, and a new study website. Development was informed by two systematic literature reviews. Feasibility and acceptability were proven in a cluster randomised control trial (ISRCTN50074817) which recruited 142 participants. The majority (74%) enrolled on at least one lifestyle behaviour change module and health improvements were observed. Almost half (43%) of those randomised to the intervention arm enrolled onto the well-being intervention. Adherence was low (7%), no one completed the full 12-week programme. A randomised control trial (ISRCTN18190978) then evaluated impact on health behaviour change, adherence and engagement, and well-being. 182 participants were recruited. Adherence remained poor (4%) however some completed the full 12-week programme. Almost half (49%) enrolled on a lifestyle behaviour change module and health improvements were observed in three modules. COVID-19 limited evaluation. The ongoing relevance of the intervention and website is evidenced through its inclusion within the Well-being In work – In work support service, Swansea Bay University Health Board.